Should central bank liquidity be a vehicle for fiscal disciplining?. (2nd May 2022) - Vestergaard, Jakob; Gabor, Daniela
Abstract: With notable exceptions, central banking scholars typically pay little attention to collateral frameworks, and therein, to the haircuts applied to the collateral assets pledged to access central bank liquidity. One such exception, Kjell Nyborg (2017) argues that the collateral policies adopted by the European Central Bank (ECB) aggravated the sovereign debt crisis and put the survival of the euro at risk. Drawing on the money view, we argue that Nyborg's critique of the ECB's crisis response is misguided and that his proposal to deepen and reinforce the ECBs role in the fiscal disciplining of member states via its collateral framework would be procyclical and destabilizing. We identify core principles for collateral policies suitable to stabilise market-based financial systems: (i) countercyclical haircuts, (ii) suspension of collateral valuation practices; and should these not be sufficient to abate collateral market liquidity strains, (iii) outright purchases of collateral assets.